Energy, exergy, economic and environmental (4E) analyses of an integrated system based on CH-CAES and electrical boiler for wind power penetration and CHP unit heat-power decoupling in wind enrichment region. (15th January 2023) - Zhao, Pan; Gou, Feifei; Xu, Wenpan; Shi, Honghui; Wang, Jiangfeng
Abstract: To improve the fluctuant renewables penetration level, the electrical energy storage (EES) technology and the flexibility improvement of combined heat and power (CHP) plant via heat-power decoupling are recognized as the two feasible solutions. Previous studies mainly focus on the single technology utilization, the combination of both technologies in one system is not involved. Therefore, an integrated system based on combined heat and compressed air energy storage (CH-CAES) and electrical boiler for wind power penetration and CHP unit heat-power decoupling in wind enrichment region is proposed. In such system, the CHP unit operates in pure condensing mode, and the heat load is mainly met by wind power via electrical boiler. The energy, exergy, economic and environmental (4E) analyses for a representative case are conducted. The results show that the proposed system can enlarge the CHP unit operation flexibility and reduce the wind curtailment. Both the energy and exergy efficiencies are boosted. Furthermore, compared with the conventional system, the levelized cost of electricity (LCOE) and the levelized cost of heat (LCOH) in proposed system decrease by 38.9% and 23.71%, respectively. Moreover, the proposed system can decrease the coal consumption effectively, leading to a remarkable reduced CO2 and SO2 emissions. Highlights: An integration of CH-CAES and electrical boiler for wind penetration is proposed. This integrated system can realize CHP unit heat-power decoupling simultaneously. Energy, exergy, economic and environmental analyses are conducted. This integrated system exhibits superior performance on multi-dimension.